A Giant Intrathoracic Malignant Schwannoma Causing Respiratory Failure in a Patient without von Recklinghausen's Disease. (28th March 2016) - Angelopoulos, Epameinondas; Eleftheriou, Konstantinos; Kyriakopoulos, Georgios; Athanassiadi, Kalliopi; Rontogianni, Dimitra; Routsi, Christina
Abstract : We report an unusual case of a thoracic opacity due to a huge mediastinal malignant schwannoma which compressed the whole left lung and the mediastinum causing respiratory failure in a 73-year-old woman without von Recklinghausen's disease. Although the tumor was resected, the patient failed to wean from mechanical ventilation and died one month later because of multiple organ dysfunction syndrome.